2019
DOI: 10.1016/j.xphs.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Ability of Submicron- and Micron-Size Silicone Oil Droplets in Dropped Prefillable Syringes to Invoke Early- and Late-Stage Immune Responses

Abstract: a b s t r a c tA number of biopharmaceuticals are available as lyophilized formulations along with a prefilled syringe (PFS) containing water for injection (WFI). Submicron-and micron-size droplets of lubricating silicone oil (SO) applied to the inner surface of the PFS barrel might migrate into the WFI, to which protein pharmaceuticals can adsorb, potentially inducing an immune response. In the present study, we subjected siliconized cyclo-olefin polymer PFSs filled with WFI to dropping stress to simulate act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 24 publications
(33 reference statements)
2
32
0
Order By: Relevance
“…13,14 Furthermore, mechanical shockeinduced increases in the concentration of protein particles and silicone oil droplets have been shown in cell-and murine-based models to promote adverse immunogenicity to therapeutic protein products. 15 These findings support our assertion that drop stress that is insufficient to cause visible damage to biologic medications may be sufficient to cause product damage at the subvisible level, which in turn could play a role in adverse effects in patients.…”
Section: Significancesupporting
confidence: 86%
“…13,14 Furthermore, mechanical shockeinduced increases in the concentration of protein particles and silicone oil droplets have been shown in cell-and murine-based models to promote adverse immunogenicity to therapeutic protein products. 15 These findings support our assertion that drop stress that is insufficient to cause visible damage to biologic medications may be sufficient to cause product damage at the subvisible level, which in turn could play a role in adverse effects in patients.…”
Section: Significancesupporting
confidence: 86%
“…Larger or smaller pure droplets are deemed more inert, but may still cause adsorption and increased immunoreactivity to therapeutic proteins. 4 The size and shape of SO droplets were evaluated in 5 solutions: saline, bacteriostatic saline, water for injection, bacteriostatic water (all from Hospira Inc, Lake Forrest, IL), and Kybella. A negative control, glass syringe (Artiglass, Padua, Italy), a positive control (Artiglass lubricated with 0.1 mL of Siluron 2000 [Fluoron GmbH, Ulm, Germany]), and 3 brands of lubricated syringes: 1 mL Luer-Lok (Becton Dickinson, Franklin Lakes, NJ), 1 mL Luer-Lok (Saldanha Rodrigues, Manaus, Brazil), and 1 mL Luer-Slip (Injex, Ourinhos, Brazil) were tested for each solution under nonagitated or agitated (10 consecutive flicks with the needle side facing upward) conditions.…”
Section: Effect Of Injection Solutions In the Dispersion Of Syringe Lmentioning
confidence: 99%
“…The density of lotion sunscreen application is commonly lower than the area density (2 mg/cm 2 ) used to test sun protection factor (SPF) levels, leading to lower than expected photoprotection. [2][3][4] Few have examined aerosol All solvents exhibited a great number of droplets within optimal phagocytic range. Saline (0.9% sodium chloride): median, 0.9 m 2 (interquartile range [IQR], 0.5-1.6 m 2 ; maximum area [max], 7.6 m 2 ); with agitation, 1.2 m 2 (IQR, 0.8-1.9 m 2 ; max, 8.6 m 2 ).…”
Section: Spray Sunscreen: Characterizing Application Area Density Andmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Our recent study showed that pharmaceutical proteins adsorb to the surface of submicron-and micron-size droplets of lubricating silicone oil (SO) that migrate into the solution from the inner surface of the PFS barrel, and that the resulting complexes are capable of invoking immune responses. 18 Therefore, the detection and quantification of protein aggregates in biopharmaceutical products together with strategies to prevent proteinaceous particle formation are necessary to mitigate the immunogenicity of biotherapeutics. 19,20 The determination of the most probable source of a stress/ perturbation can aid in the development of quality control strategies.…”
Section: Introductionmentioning
confidence: 99%